Cementing material capable of comprehensively utilizing solid waste and preparation method of cementing material
By scientifically proportioning and alkali-exciting treatment of solid waste desulfurization gypsum, cement clinker, water slag/mine powder and ferrosilicon ash, high-strength gelling materials were prepared, which solved the limited source of gelling materials and solid waste. The problem of insufficient utilization has achieved the improvement of resource utilization and environmental benefits.
Patent Information
- Application Number
- CN202411697228.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2024-12-27
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing gelling material formulations and preparation methods have problems with limited sources of raw materials and high costs, and industrial solid waste such as desulfurization gypsum, water slag and ferrosilicon ash have failed to achieve high value-added utilization, resulting in waste of resources and environmental pollution.
By scientifically proportioning the raw materials such as solid waste desulfurization gypsum, cement clinker, water slag/orch powder and ferrosilicon ash, and adding alkali excitation catalysts, high-strength gelling materials are prepared, and mechanical molding and vibration deposition processes are used. Form a gelled material with high flexural resistance and compressive strength.
The resource utilization of solid waste has been achieved, production costs have been reduced, the comprehensive performance of concrete has been improved, the dependence on natural resources has been reduced, and the problems of solid waste accumulation and environmental pollution have been effectively solved.
Smart Images

Figure CN119191809A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of gel material preparation, and in particular relates to a gelling material for comprehensive utilization of solid waste and a preparation method thereof. Background Art
[0002] The solid waste generated by the five major industries of my country, namely, the production and supply of electricity and heat, ferrous metal smelting and rolling processing, non-ferrous metal mining and dressing, coal mining and washing, and ferrous metal mining and dressing, accounts for nearly 80% of the total. The large amount of industrial solid waste that has been accumulated and newly generated every year in my country not only occupies precious land resources, but also causes varying degrees of pollution to the soil, water and atmosphere.
[0003] Among building materials, cementitious materials can be transformed from a slurry into a solid stone-like body through a series of physical and chemical reactions, and can cement other solid materials into a whole with a certain mechanical strength. Through its own physical and chemical reactions, in the process of changing from a plastic slurry to a hard stone-like body, it can bond loose granular and blocky materials into a whole. The main characteristics of cementitious materials are light bulk density, high strength, high refractoriness, high load softening temperature, good chemical stability, large specific surface area, etc. However, some cementitious material formulas and preparation methods have been disclosed in patent literature in recent years. Common problems include limited raw material sources and high costs. Summary of the invention
[0004] In view of the above-mentioned deficiencies of the prior art, the present invention provides a gelling material for comprehensive utilization of solid waste and a preparation method thereof.
[0005] Preparation of desulfurized gypsum The wet limestone-gypsum method is currently the most widely used flue gas desulfurization process. The use of wet desulfurization method to treat flue gas will produce a large amount of desulfurized gypsum. The treatment and comprehensive utilization of desulfurized gypsum is one of the key factors affecting the promotion of wet desulfurization technology in my country. With the large-scale commissioning of flue gas desulfurization technology in my country, coal-fired power plants will emit more and more desulfurized gypsum. At present, a considerable part of it is still mainly stored in piles. It has become the second largest solid waste after fly ash in thermal power plants, which not only occupies land resources, but also is harmful to the environment. If it can be fully utilized to replace part of natural gypsum, it can not only save natural resources but also make the waste around the power plant resource-based. The comprehensive utilization of desulfurized gypsum and its gradual industrial production application can unify the benefits of power plants, environmental benefits, and social benefits.
[0006] Ferrosilicon ash is an industrial waste residue formed by collecting and treating the smoke and dust that escapes with the exhaust gas during the smelting of ferrosilicon alloy through special capture devices. There are many ferrosilicon production enterprises in my country, and a large amount of ferrosilicon ash is produced every year. At present, the large amount of ferrosilicon ash accumulation has caused serious pollution to the environment. Ferrosilicon ash contains a large amount of amorphous silicon oxides. At present, the use of ferrosilicon ash is mainly as an additive for cement and refractory materials, an adhesive for metallurgical pellets, a dispersant for chemical products, a filler for rubber and plastics, a plastic sealing material for the electronics industry, and a casting for the electrical industry. However, these technologies cannot make high-value-added use of ferrosilicon ash, so it is necessary to seek new methods to comprehensively utilize ferrosilicon ash.
[0007] Water slag is a very good active admixture, but due to its high hardness and poor abrasiveness, only a small amount is currently used as a cement admixture by cement manufacturers, and most steel mills pile up water slag as waste, which not only occupies a large amount of arable land, but also pollutes the environment. Blast furnace slag is a molten silicate material discharged from the blast furnace when smelting pig iron; when smelting in a blast furnace, iron ore, fuel (coke) and flux are added from the top of the furnace. When the temperature in the furnace reaches 1400-1500℃, the material melts and becomes a liquid phase. The slag floating on the molten iron in the liquid phase is separated through the iron mouth through the main iron ditch slag skimmer or discharged from the slag mouth. This is blast furnace slag. Blast furnace slag is composed of gangue, ash, flux and other impurities that cannot enter pig iron. It is a fusible mixture. There are three main ways to treat blast furnace slag: naturally cool the high-temperature slag to become hard dry slag; use water quenching to crush the high-temperature liquid slag to become loose water slag; use steam or compressed air to disperse the high-temperature liquid slag to become fluffy slag cotton.
[0008] Cement clinker is a semi-finished product obtained by mixing limestone, clay and iron raw materials in appropriate proportions, burning them until they are partially or completely melted, and cooling them. In the cement industry, the most commonly used silicate cement clinker has calcium oxide, silicon dioxide and a small amount of aluminum oxide and iron oxide as its main chemical components. The main mineral components are tricalcium silicate, dicalcium silicate, tricalcium aluminate and tetracalcium aluminoferrite. After silicate cement clinker is ground with an appropriate amount of gypsum, it becomes silicate cement. The calcination of cement clinker is a complex high-temperature reaction process between gas-solid, liquid-solid and solid-solid phases. There is not only the decomposition of certain natural minerals, but also the synthesis of many oxides. The variety, quantity and characteristics of the final formed minerals, namely clinker, must meet the requirements of the specifications to ensure that the finished product can achieve the established performance indicators. Although the total theoretical heat consumption of the calcination process is not much, the actual fuel consumption per unit product is relatively high due to the high reaction temperature required.
[0009] Mineral powder is the most active admixture in cement at present. It is a molten product with silicate and aluminosilicate as the main components, and is obtained by quenching. It has "potential hydraulic hardness" and is hydraulically hardened when stimulated by lime, clinker powder, alkali and gypsum. However, due to the high temperature water, 80%-90% of the minerals are glass, and its structure is mostly Si-O bonds, so it is difficult to grind. With the abolition of PO32.5 cement and the development of composite cement, there is a lot of room for admixtures to enter the market. However, due to the characteristics of the vertical kiln clinker calcination process, the flux minerals of the vertical kiln clinker are more than those of the rotary kiln clinker, the relative CS content is not as much as that of the rotary kiln clinker, and the f-CaO in the vertical kiln clinker is higher than that in the rotary kiln clinker. Therefore, the amount of admixture added is subject to certain restrictions. In cement production, clinker and slag are usually ground together. The disadvantage is that when the clinker reaches the required fineness, the slag still cannot reach a sufficient fineness, and its activity cannot be fully exerted, which also causes a waste of clinker resources and slag resources.
[0010] The present invention increases the flexural strength and compressive strength of cement mortar strips by adding solid waste desulfurization gypsum, cement clinker, slag / mineral powder, ferrosilicon ash and other raw materials and then adding an alkali activator; their application methods are similar and their principles are interconnected, and multiple solid wastes are used in concrete in a composite manner to give full play to the advantages of each component, which is helpful to improve the comprehensive performance of concrete; the addition of alkali-activated catalyst plays an important role in the strength of mortar strips and greatly reduces the cost budget.
[0011] Specifically, the technical solution adopted by the present invention is: In a first aspect, the present invention provides a gelling material for comprehensive utilization of solid waste, comprising a gelling main material and an alkali-activated catalyst, wherein the weight of the alkali-activated catalyst accounts for 5-9% of the weight of the gelling main material; The cementitious main material comprises the following raw materials in parts by weight: 0.05-0.15 parts of cement clinker powder, 0.05-0.15 parts of desulfurized gypsum, 0.1-1 parts of slag / mineral powder, 0.1-0.15 parts of ferrosilicon ash, and 0.008-0.016 parts of reinforcing additives.
[0012] As a further illustration of the present invention, the reinforcing aid is composed of 0.004-0.008 parts by weight of calcium oxalate and 0.004-0.008 parts by weight of sodium thiosulfate.
[0013] As a further illustration of the present invention, the alkali-activated catalyst is calcium carbide or calcium hydroxide.
[0014] The second aspect of the present invention provides a method for preparing the above-mentioned cementitious material for comprehensive utilization of solid waste, comprising the following steps: S1. Mixing ingredients: grind and sieve the dried cement clinker powder, desulfurized gypsum, slag / mineral powder, and ferrosilicon ash through a ball mill for later use; S2, dispersing and mixing: weighing the raw materials of the gel main material according to the ratio of the raw materials, and evenly mixing them together to obtain the gel main material, and then adding 5-9% of the weight of the gel main material to the base-activated catalyst to obtain the gel dispersion; S3, mechanical forming: adding water to the gelled dispersion obtained in S2 and stirring to form mortar; S4, mechanical compaction: the mortar obtained in S3 is formed into a test mold and compacted to obtain a mortar test block; S5, curing: curing the mortar test block obtained in S4; S6. Finished product: taking out the test block sample cured in S5 and demoulding it to obtain the cementitious material test block sample for comprehensive utilization of solid waste.
[0015] As a further illustration of the present invention, in S1, cement clinker powder, desulfurized gypsum, mineral powder, slag and ferrosilicon ash are dried in an electric blast drying oven at 90°C to 110°C; and the powder is ball-milled and passed through a 200-mesh sieve, with the residue being less than 5%.
[0016] As a further explanation of the present invention, in S3, a mortar mixer is used for stirring and molding, and after the gelling dispersion is stirred for 5 minutes to 8 minutes, water is added to the mixed raw materials and stirring is continued, wherein the mass ratio of the gelling dispersion to water is 4:1, and the total stirring time range of the mortar mixer is controlled within 10 to 15 minutes.
[0017] As a further illustration of the present invention, the mechanical compaction process of S4 specifically includes: After the mortar is prepared, it is immediately molded. The empty test mold and mold sleeve are fixed on the vibration table. Use a spoon to load the mortar into the test mold in two layers directly from the mixing pot. When loading the first layer, put about 300g of mortar in each groove, and use a large spreader vertically placed on the top of the mold sleeve to spread the material layer back and forth along each mold groove once, then vibrate for 60s, then load the second layer of mortar, spread it flat with a small spreader, and then vibrate for 180s, resonate and compact for 240s, remove the mold sleeve, take down the test mold from the vibration table, and mark the test mold number.
[0018] As a further explanation of the present invention, the curing process of S5 specifically includes: The marked mortar test blocks shall be immediately placed horizontally or vertically in 20±1℃ water for curing, and the water shall be in contact with the six surfaces of the mortar test blocks; during the curing period, the distance between the mortar test blocks and the water depth on the upper surface of the mortar test blocks shall not be less than 5mm.
[0019] Compared with the prior art, the present invention has the following advantages: The present invention increases the flexural strength and compressive strength of cement mortar specimens by adding solid waste desulfurization gypsum, cement clinker, slag / mineral powder, slag, ferrosilicon ash and other solid waste raw materials and then adding an alkali-activated catalyst; high-strength test block samples are prepared through scientific proportioning and reasonable processes, and the raw materials are widely distributed, easy to obtain and low in cost; the firing temperature in the preparation process is low, which saves energy; the prepared product has high strength and small specific surface area.
[0020] The present invention turns solid waste such as desulfurized gypsum, slag / mineral powder and ferrosilicon ash into treasure, which helps to improve the comprehensive performance of concrete. The formula composition is designed as a calcium-aluminum-magnesium system, ingredient mixing and solid waste application. The combination of the three greatly reduces the cost budget and has excellent performance, and can obtain good economic benefits. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 It is a flow chart for preparing a cementitious material for comprehensive utilization of solid waste provided by an embodiment of the present invention. DETAILED DESCRIPTION
[0022] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0023] Cement clinker is made of limestone, clay and iron as main raw materials; the wet limestone-gypsum method for preparing desulfurized gypsum is currently the most widely used flue gas desulfurization process; mineral powder is currently the most active admixture in cement, which is a melt with silicate and aluminosilicate as main components; ferrosilicon ash is an industrial waste residue formed by collecting and treating the smoke escaping with the exhaust gas during the smelting of ferrosilicon alloy through a special capture device; water slag is a very good active admixture, but due to its high hardness and poor grindability, currently only a small amount is used as a cement admixture by cement manufacturers.
[0024] Main ingredients of raw materials used in examples and comparative examples raw material Main Ingredients Cement clinker powder <![CDATA[Weight content: Al2O3: 5.54%, SiO2: 23.72%, CaO: 60.1%, Fe2O3: 3.17%; the oxides of the remaining components account for 7.47%.]]> Desulfurization gypsum <![CDATA[pH value: 7.35; Weight content: CaSO4·2H2O: 82.17%; CaCO3: 6.42%; Oxides of the remaining components account for 11.41%.]]> Ferrosilicon ash <![CDATA[Weight content: Al2O3: 2%, SiO2: 89%, CaO: 1%, MgO: 2%, and the oxides of the remaining components account for 6%.]]> Slag / Mineral powder <![CDATA[Weight content: Al2O3: 14.44%, SiO2: 33.93%, CaO: 34.14%, TiO: 1.32%; Fe2O3: 0.62%, MgO: 11.2%; The oxides of the remaining components account for 4.35%.]]> Example 1
[0025] like Figure 1 As shown, this embodiment provides a method for preparing a cementitious material for comprehensive utilization of solid waste, comprising the following steps: S1. Mixing ingredients: Cement clinker powder, solid waste desulfurization gypsum, slag and ferrosilicon ash are dried in a 90°C electric blast drying oven. The dried solid waste raw materials are appropriately crushed and ball-milled, and then passed through a 200-mesh sieve respectively. The sieve residue is less than 5%, and then packaged for use.
[0026] S2. Dispersion and mixing: According to the weight percentage composition: 0.12 parts of cement clinker powder, 0.13 parts of desulfurized gypsum, 0.1 parts of slag, 0.13 parts of ferrosilicon ash, 0.004 parts of calcium oxalate and 0.004 parts of sodium thiosulfate are weighed and evenly mixed together, and then 7% of the weight of the above mixture is added with an alkali activator (calcium carbide) to obtain a gelled dispersion.
[0027] S3, mechanical molding: The gelled dispersion obtained in S2 is molded by stirring with a mortar mixer. After stirring for 5 minutes, water is added to the mixed raw materials (m (gelled dispersion): m (water) = 4:1) and stirring is continued. The total stirring time of the mortar mixer is controlled within 10 minutes to finally obtain mortar.
[0028] S4, Mechanical compaction: Immediately shape the mortar prepared in S3, fix the empty test mold and mold sleeve on the compaction table, use a spoon to directly load the mortar from the mixing pot into the test mold in two layers. When loading the first layer, put about 300g of mortar in each groove, use a large spreader vertically on the top of the mold sleeve to spread the material layer back and forth along each mold groove once, and then vibrate for 60s. Then load the second layer of mortar, use a small spreader to spread it flat, and then vibrate for 180s. Resonance compaction for 240s. Remove the mold sleeve, take down the test mold from the compaction table, and mark the test mold number.
[0029] S5. Curing: Place the marked specimens horizontally or vertically in 20℃ water for curing immediately. When placed horizontally, the scraped surface should face upwards. The specimens are placed on a non-perishable grate and kept at a certain distance from each other so that water can contact the six faces of the specimens. During the curing period, the interval between the specimens or the water depth on the upper surface of the specimens shall not be less than 5mm. Each curing tank only cures cement specimens of the same type. Initially fill the curing tank (or container) with tap water, and then add water at any time to maintain an appropriate constant water level. It is not allowed to completely change the water during the curing period. Except for specimens that are 24h old or delayed to 48h for demolding, any specimens that have reached the age should be removed from the water 15min before the test (breaking). Wipe off the sediment on the surface of the specimen and cover it with a wet cloth until the test.
[0030] S6. Finished product: After curing, record the initial setting time and final setting time of the test block sample, take it out and demould it to obtain the high-strength cementitious material test block sample.
[0031] Table 1 Performance test results of the test block samples obtained in Example 1
[0032] Example 2 like Figure 1 As shown, this embodiment provides a method for preparing a cementitious material for comprehensive utilization of solid waste, comprising the following steps: S1. Mixing ingredients: Cement clinker powder, solid waste desulfurization gypsum, slag and ferrosilicon ash are dried in an electric blast drying oven at 100°C. The dried solid waste raw materials are appropriately crushed and ball-milled, and then sieved through a 200-mesh sieve respectively. The sieve residue is less than 5%, and then packaged for use.
[0033] S2. Dispersion and mixing: According to the weight percentage composition: 0.15 parts of cement clinker powder, 0.1 parts of desulfurized gypsum, 1 part of slag, 0.15 parts of ferrosilicon ash, 0.006 parts of calcium oxalate, and 0.008 parts of sodium thiosulfate are weighed and evenly mixed together, and then 5% of the weight of the above mixture is added. Alkali activator (calcium hydroxide) to obtain a gelled dispersion.
[0034] S3, mechanical molding: The gelled dispersion obtained in S2 is molded by stirring with a mortar mixer. After stirring for 7 minutes, water is added to the mixed raw materials (m (gelled dispersion): m (water) = 4:1) and stirring is continued. The total stirring time of the mortar mixer is controlled within 12 minutes to finally obtain mortar.
[0035] S4, Mechanical compaction: Immediately shape the mortar prepared in S3, fix the empty test mold and mold sleeve on the compaction table, use a spoon to directly load the mortar from the mixing pot into the test mold in two layers. When loading the first layer, put about 300g of mortar in each groove, use a large spreader vertically on the top of the mold sleeve to spread the material layer back and forth along each mold groove once, and then vibrate for 60s. Then load the second layer of mortar, use a small spreader to spread it flat, and then vibrate for 180s. Resonance compaction for 240s. Remove the mold sleeve, take down the test mold from the compaction table, and mark the test mold number.
[0036] S5. Curing: Place the marked specimens horizontally or vertically in 20℃ water for curing immediately. When placed horizontally, the scraped surface should face upwards. The specimens are placed on a non-perishable grate and kept at a certain distance from each other so that water can contact the six faces of the specimens. During the curing period, the interval between the specimens or the water depth on the upper surface of the specimens shall not be less than 5mm. Each curing tank only cures cement specimens of the same type. Initially fill the curing tank (or container) with tap water, and then add water at any time to maintain an appropriate constant water level. It is not allowed to completely change the water during the curing period. Except for specimens that are 24h old or delayed to 48h for demolding, any specimens that have reached the age should be removed from the water 15min before the test (breaking). Wipe off the sediment on the surface of the specimen and cover it with a wet cloth until the test.
[0037] S6. Finished product: After curing, record the initial setting time and final setting time of the test block sample, take it out and demould it to obtain the high-strength cementitious material test block sample.
[0038] Table 2 Performance test results of the test block samples obtained in Example 2
[0039] Example 3 like Figure 1 As shown, this embodiment provides a method for preparing a cementitious material for comprehensive utilization of solid waste, comprising the following steps: S1. Mixing ingredients: Dry cement clinker powder, solid waste desulfurization gypsum, slag and ferrosilicon ash in an electric blast drying oven at 110°C. After proper crushing and ball milling, the dried solid waste raw materials are sieved through 200 mesh sieves respectively. The sieve residue is less than 5% and packaged for later use.
[0040] S2. Dispersion and mixing: According to the weight percentage composition: 0.05 part of cement clinker powder, 0.12 part of desulfurized gypsum, 0.5 part of slag, 0.1 part of ferrosilicon ash, 0.005 part of calcium oxalate, and 0.007 part of sodium thiosulfate, weigh the materials and mix them evenly, then add 8% of the weight of the mixture of alkali activator (calcium carbide powder) to obtain a gelled dispersion.
[0041] S3, mechanical molding: The gelled dispersion obtained in S2 is molded by stirring with a mortar mixer. After stirring for 8 minutes, water is added to the mixed raw materials (m (gelled dispersion): m (water) = 4:1) and stirring is continued. The total stirring time of the mortar mixer is controlled within 15 minutes to finally obtain mortar.
[0042] S4, Mechanical compaction: Immediately shape the mortar prepared in S3, fix the empty test mold and mold sleeve on the compaction table, use a spoon to directly load the mortar from the mixing pot into the test mold in two layers. When loading the first layer, put about 300g of mortar in each groove, use a large spreader vertically on the top of the mold sleeve to spread the material layer back and forth along each mold groove once, and then vibrate for 60s. Then load the second layer of mortar, use a small spreader to spread it flat, and then vibrate for 180s. Resonance compaction for 240s. Remove the mold sleeve, take down the test mold from the compaction table, and mark the test mold number.
[0043] S5. Curing: Place the marked specimens horizontally or vertically in 20℃ water for curing immediately. When placed horizontally, the scraped surface should face upwards. The specimens are placed on a non-perishable grate and kept at a certain distance from each other so that water can contact the six faces of the specimens. During the curing period, the interval between the specimens or the water depth on the upper surface of the specimens shall not be less than 5mm. Each curing tank only cures cement specimens of the same type. Initially fill the curing tank (or container) with tap water, and then add water at any time to maintain an appropriate constant water level. It is not allowed to completely change the water during the curing period. Except for specimens that are 24h old or delayed to 48h for demolding, any specimens that have reached the age should be removed from the water 15min before the test (breaking). Wipe off the sediment on the surface of the specimen and cover it with a wet cloth until the test.
[0044] S6. Finished product: After curing, record the initial setting time and final setting time of the test block sample, take it out and demould it to obtain the high-strength cementitious material test block sample.
[0045] Table 3 Performance test results of the test block samples obtained in Example 3
[0046] Example 4 like Figure 1 As shown, this embodiment provides a method for preparing a cementitious material for comprehensive utilization of solid waste, comprising the following steps: S1. Mixing ingredients: Dry cement clinker powder, solid waste desulfurization gypsum, mineral powder and ferrosilicon ash in an electric blast drying oven at 110°C. After proper crushing and ball milling, the dried solid waste raw materials are sieved through 200 mesh sieves respectively. The sieve residue is less than 5% and packaged for later use.
[0047] S2. Dispersion and mixing: The following compositions are prepared in weight percentage: 0.13 parts of cement clinker powder, 0.05 parts of desulfurized gypsum, 0.8 parts of mineral powder, 0.14 parts of ferrosilicon ash, 0.007 parts of calcium oxalate and 0.006 parts of sodium thiosulfate. The materials are weighed and evenly mixed together, and then 9% of the weight of the mixture of alkali activator (calcium hydroxide) is added to obtain a gelled dispersion.
[0048] S3, mechanical molding: The gelled dispersion obtained in S2 is molded by stirring with a mortar mixer. After stirring for 8 minutes, water is added to the mixed raw materials (m (gelled dispersion): m (water) = 4:1) and stirring is continued. The total stirring time of the mortar mixer is controlled within 15 minutes to finally obtain mortar.
[0049] S4, Mechanical compaction: Immediately shape the mortar prepared in S3, fix the empty test mold and mold sleeve on the compaction table, use a spoon to directly load the mortar from the mixing pot into the test mold in two layers. When loading the first layer, put about 300g of mortar in each groove, use a large spreader vertically on the top of the mold sleeve to spread the material layer back and forth along each mold groove once, and then vibrate for 60s. Then load the second layer of mortar, use a small spreader to spread it flat, and then vibrate for 180s. Resonance compaction for 240s. Remove the mold sleeve, take down the test mold from the compaction table, and mark the test mold number.
[0050] S5. Curing: Place the marked specimens horizontally or vertically in 20℃ water for curing immediately. When placed horizontally, the scraped surface should face upwards. The specimens are placed on a non-perishable grate and kept at a certain distance from each other so that water can contact the six faces of the specimens. During the curing period, the interval between the specimens or the water depth on the upper surface of the specimens shall not be less than 5mm. Each curing tank only cures cement specimens of the same type. Initially fill the curing tank (or container) with tap water, and then add water at any time to maintain an appropriate constant water level. It is not allowed to completely change the water during the curing period. Except for specimens that are 24h old or delayed to 48h for demolding, any specimens that have reached the age should be removed from the water 15min before the test (breaking). Wipe off the sediment on the surface of the specimen and cover it with a wet cloth until the test.
[0051] S6. Finished product: After curing, record the initial setting time and final setting time of the test block sample, take it out and demould it to obtain the high-strength cementitious material test block sample.
[0052] Table 4 Performance test results of the test block samples obtained in Example 4
[0053] Example 5 like Figure 1 As shown, this embodiment provides a method for preparing a cementitious material for comprehensive utilization of solid waste, comprising the following steps: S1. Mixing ingredients: Dry cement clinker powder, solid waste desulfurization gypsum, mineral powder and ferrosilicon ash in an electric blast drying oven at 110°C. After proper crushing and ball milling, the dried solid waste raw materials are sieved through 200 mesh sieves respectively. The sieve residue is less than 5% and packaged for later use.
[0054] S2. Dispersion and mixing: According to the weight percentage composition: 0.1 part of cement clinker powder, 0.15 part of desulfurized gypsum, 0.7 part of mineral powder, 0.12 part of ferrosilicon ash, 0.008 part of calcium oxalate, and 0.005 part of sodium thiosulfate, weigh the materials and mix them evenly, then add 5% of the weight of the mixture of alkali activator (calcium carbide powder) to obtain a gelled dispersion.
[0055] S3, mechanical molding: The gelled dispersion obtained in S2 is molded by stirring with a mortar mixer. After stirring for 5 minutes, water is added to the mixed raw materials (m (gelled dispersion): m (water) = 4:1) and stirring is continued. The total stirring time of the mortar mixer is controlled within 10 minutes to finally obtain mortar.
[0056] S4, Mechanical compaction: Immediately shape the mortar prepared in S3, fix the empty test mold and mold sleeve on the compaction table, use a spoon to directly load the mortar from the mixing pot into the test mold in two layers. When loading the first layer, put about 300g of mortar in each groove, use a large spreader vertically on the top of the mold sleeve to spread the material layer back and forth along each mold groove once, and then vibrate for 60s. Then load the second layer of mortar, use a small spreader to spread it flat, and then vibrate for 180s. Resonance compaction for 240s. Remove the mold sleeve, take down the test mold from the compaction table, and mark the test mold number.
[0057] S5. Curing: Place the marked specimens horizontally or vertically in 20℃ water for curing immediately. When placed horizontally, the scraped surface should face upwards. The specimens are placed on a non-perishable grate and kept at a certain distance from each other so that water can contact the six faces of the specimens. During the curing period, the interval between the specimens or the water depth on the upper surface of the specimens shall not be less than 5mm. Each curing tank only cures cement specimens of the same type. Initially fill the curing tank (or container) with tap water, and then add water at any time to maintain an appropriate constant water level. It is not allowed to completely change the water during the curing period. Except for specimens that are 24h old or delayed to 48h for demolding, any specimens that have reached the age should be removed from the water 15min before the test (breaking). Wipe off the sediment on the surface of the specimen and cover it with a wet cloth until the test.
[0058] S6. Finished product: After curing, record the initial setting time and final setting time of the test block sample, take it out and demould it to obtain the high-strength cementitious material test block sample.
[0059] Table 5 Performance test results of the test block samples obtained in Example 5
[0060] Comparative Example 1 This comparative example provides a method for preparing a gelling material, comprising the following steps: S1. Mixing ingredients: Dry the solid waste desulfurization gypsum, slag and ferrosilicon ash in a 90℃ electric blast drying oven, crush and ball-mill the dried solid waste materials appropriately, and then pass them through a 200-mesh sieve respectively. The sieve residue is less than 5%, and then packaged for use.
[0061] S2. Dispersion and mixing: According to the composition in parts: 0.12 parts of cement clinker powder, 0.13 parts of desulfurized gypsum, 0.1 parts of slag, 0.05 parts of ferrosilicon ash, 0.004 parts of calcium oxalate and 0.004 parts of sodium thiosulfate, weigh the materials and mix them evenly, then add 15% of the weight of the mixture of alkali activator (calcium carbide) to obtain a gelled dispersion.
[0062] S3, mechanical molding: The gelled dispersion obtained in S2 is molded by stirring with a mortar mixer. After stirring for 5 minutes, water is added to the mixed raw materials (m (gelled dispersion): m (water) = 4:1) and stirring is continued. The total stirring time of the mortar mixer is controlled within 10 minutes to finally obtain mortar.
[0063] S4, Mechanical compaction: Immediately shape the mortar prepared in S3, fix the empty test mold and mold sleeve on the compaction table, use a spoon to directly load the mortar from the mixing pot into the test mold in two layers. When loading the first layer, put about 300g of mortar in each groove, use a large spreader vertically on the top of the mold sleeve to spread the material layer back and forth along each mold groove once, and then vibrate for 60s. Then load the second layer of mortar, use a small spreader to spread it flat, and then vibrate for 180s. Resonance compaction for 240s. Remove the mold sleeve, take down the test mold from the compaction table, and mark the test mold number.
[0064] S5. Curing: Place the marked specimens horizontally or vertically in 20℃ water for curing immediately. When placed horizontally, the scraped surface should face upwards. The specimens are placed on a non-perishable grate and kept at a certain distance from each other so that water can contact the six faces of the specimens. During the curing period, the interval between the specimens or the water depth on the upper surface of the specimens shall not be less than 5mm. Each curing tank only cures cement specimens of the same type. Initially fill the curing tank (or container) with tap water, and then add water at any time to maintain an appropriate constant water level. It is not allowed to completely change the water during the curing period. Except for specimens that are 24h old or delayed to 48h for demolding, any specimens that have reached the age should be removed from the water 15min before the test (breaking). Wipe off the sediment on the surface of the specimen and cover it with a wet cloth until the test.
[0065] S6. Finished product: After curing, record the initial setting time and final setting time of the test block sample, take it out and demould it to obtain the high-strength cementitious material test block sample.
[0066] Table 6 Performance test results of the test block samples obtained in Comparative Example 1
[0067] In Comparative Example 1, compared with Example 1, adding an excessive amount of alkali activator reduces the mechanical strength of the product and significantly prolongs the solidification time of the product.
[0068] Comparative Example 2 This comparative example provides a method for preparing a gelling material, comprising the following steps: S1. Mixing ingredients: Cement clinker powder, solid waste desulfurization gypsum, slag and ferrosilicon ash are dried in a 90°C electric blast drying oven. The dried solid waste raw materials are appropriately crushed and ball-milled, and then passed through a 200-mesh sieve respectively. The sieve residue is less than 5%, and then packaged for use.
[0069] S2. Dispersion and mixing: According to the weight percentage composition: 0.05 part of cement clinker powder, 0.12 part of desulfurized gypsum, 0.5 part of slag, and 0.1 part of ferrosilicon ash are weighed and evenly mixed together, and then 8% of the weight of the mixture (calcium carbide powder) is added to obtain a gelled dispersion.
[0070] S3, mechanical molding: The gelled dispersion obtained in S2 is molded by stirring with a mortar mixer. After stirring for 5 minutes, water is added to the mixed raw materials (m (gelled dispersion): m (water) = 4:1) and stirring is continued. The total stirring time of the mortar mixer is controlled within 10 minutes to finally obtain mortar.
[0071] S4, Mechanical compaction: Immediately shape the mortar prepared in S3, fix the empty test mold and mold sleeve on the compaction table, use a spoon to directly load the mortar from the mixing pot into the test mold in two layers. When loading the first layer, put about 300g of mortar in each groove, use a large spreader vertically on the top of the mold sleeve to spread the material layer back and forth along each mold groove once, and then vibrate for 60s. Then load the second layer of mortar, use a small spreader to spread it flat, and then vibrate for 180s. Resonance compaction for 240s. Remove the mold sleeve, take down the test mold from the compaction table, and mark the test mold number.
[0072] S5. Curing: Place the marked specimens horizontally or vertically in 20℃ water for curing immediately. When placed horizontally, the scraped surface should face upwards. The specimens are placed on a non-perishable grate and kept at a certain distance from each other so that water can contact the six faces of the specimens. During the curing period, the interval between the specimens or the water depth on the upper surface of the specimens shall not be less than 5mm. Each curing tank only cures cement specimens of the same type. Initially fill the curing tank (or container) with tap water, and then add water at any time to maintain an appropriate constant water level. It is not allowed to completely change the water during the curing period. Except for specimens that are 24h old or delayed to 48h for demolding, any specimens that have reached the age should be removed from the water 15min before the test (breaking). Wipe off the sediment on the surface of the specimen and cover it with a wet cloth until the test.
[0073] S6. Finished product: After curing, record the initial setting time and final setting time of the test block sample, take it out and demould it to obtain the high-strength cementitious material test block sample.
[0074] Table 7 Performance test results of the test block samples obtained in Comparative Example 2
[0075] In Comparative Example 2, Comparative Example 2 is compared with Example 3. The lack of reinforcing additives results in a decrease in the mechanical strength of the product, the 28d compressive strength is reduced to 12.7 MPa, and the solidification time is significantly prolonged.
[0076] Comparative Example 3
[0077] This comparative example provides a method for preparing a gelling material, comprising the following steps: S1. Mixing ingredients: Dry cement clinker powder, solid waste desulfurization gypsum and ferrosilicon ash in a 90°C electric blast drying oven, crush and ball-mill the dried solid waste materials appropriately, and then pass through a 200-mesh sieve respectively. The sieve residue is less than 5%, and then packaged for use.
[0078] S2. Dispersion and mixing: According to the weight percentage composition: 0.1 part of cement clinker powder, 0.15 part of desulfurized gypsum, 0.12 part of ferrosilicon ash, 0.008 part of calcium oxalate, and 0.005 part of sodium thiosulfate, weigh the materials and mix them evenly, then add 5% of the weight of the mixture of alkali activator (calcium carbide powder) to obtain a gelled dispersion.
[0079] S3, mechanical molding: The gelled dispersion obtained in S2 is molded by stirring with a mortar mixer. After stirring for 5 minutes, water is added to the mixed raw materials (m (gelled dispersion): m (water) = 4:1) and stirring is continued. The total stirring time of the mortar mixer is controlled within 10 minutes to finally obtain mortar.
[0080] S4, Mechanical compaction: Immediately shape the mortar prepared in S3, fix the empty test mold and mold sleeve on the compaction table, use a spoon to directly load the mortar from the mixing pot into the test mold in two layers. When loading the first layer, put about 300g of mortar in each groove, use a large spreader vertically on the top of the mold sleeve to spread the material layer back and forth along each mold groove once, and then vibrate for 60s. Then load the second layer of mortar, use a small spreader to spread it flat, and then vibrate for 180s. Resonance compaction for 240s. Remove the mold sleeve, take down the test mold from the compaction table, and mark the test mold number.
[0081] S5. Curing: Place the marked specimens horizontally or vertically in 20℃ water for curing immediately. When placed horizontally, the scraped surface should face upwards. The specimens are placed on a non-perishable grate and kept at a certain distance from each other so that water can contact the six faces of the specimens. During the curing period, the interval between the specimens or the water depth on the upper surface of the specimens shall not be less than 5mm. Each curing tank only cures cement specimens of the same type. Initially fill the curing tank (or container) with tap water, and then add water at any time to maintain an appropriate constant water level. It is not allowed to completely change the water during the curing period. Except for specimens that are 24h old or delayed to 48h for demolding, any specimens that have reached the age should be removed from the water 15min before the test (breaking). Wipe off the sediment on the surface of the specimen and cover it with a wet cloth until the test.
[0082] S6. Finished product: After curing, record the initial setting time and final setting time of the test block sample, take it out and demould it to obtain the high-strength cementitious material test block sample.
[0083] Table 8 Performance test results of the test block samples obtained in Comparative Example 3
[0084] In Comparative Example 3, which is compared with Example 5, the lack of mineral powder causes the mechanical strength of the product to decrease, and the solidification time does not change much.
[0085] From the performance test results of the test block samples obtained after the experimental preparation of Comparative Examples 1-3 and Examples 1, 3, and 5, it can be seen that the addition of excessive alkali activator reduces the strength of the product; and the absence of reinforcing additives greatly reduces the strength of the product and prolongs the solidification time; the absence of mineral powder significantly reduces the mechanical properties of the product.
[0086] In summary, by adding solid waste desulfurized gypsum, cement clinker, slag / mineral powder, ferrosilicon ash and other raw materials and then adding alkali-activated catalyst, the flexural strength and compressive strength of cement mortar specimens can be increased; their application methods are similar and their principles are interoperable. Solid waste and ferrosilicon ash are added to cement to significantly improve the compressive strength of concrete; in summary, the present invention has the following advantages: 1. The main raw materials of the present invention are cement clinker powder, desulfurized gypsum, slag / ore powder, ferrosilicon ash and other solid waste raw materials (≥80%), which are industrial solid wastes. The raw materials are widely distributed, easy to obtain and low in cost.
[0087] 2. The preparation process is simple and energy-saving.
[0088] By adding solid waste desulfurized gypsum, cement clinker, mineral powder / water slag, ferrosilicon ash and other raw materials, and then adding alkali-activated catalysts, the flexural strength and compressive strength of cement mortar specimens can be increased; their application methods are similar and the principles are interoperable. The improvement of compressive strength is due to the composite filling effect of solid waste and ferrosilicon ash and the volcanic ash effect, which makes the microstructure of the slurry denser; the impermeability and resistance to chloride ion penetration are good. The use of slag / mineral powder as concrete can improve the mechanical properties and durability of concrete, not only because the slag itself has a high hardness, but another important reason is that the surface of the tailings rich in silicon and aluminum elements is similar to slag, which has potential activity and can participate in the hydration reaction under the stimulation of alkaline conditions or high temperature conditions. And the composite use of multiple solid wastes in concrete can bring out the advantages of each component, which helps to improve the comprehensive performance of concrete; it can also improve the flexural and compressive properties of concrete mortar specimens and reduce the bulk density, etc.; because the cement clinker is decomposed and burned after high-temperature calcination, it is reasonably configured with other solid waste raw materials and added to pure water and stirred evenly, and the calcium oxalate as an early strength agent and sodium thiosulfate as a reducing agent react with water to react with water, so that the strength of the concrete mortar specimens is greatly improved.
[0089] The addition of alkali-activated catalyst plays a key role in the strength of mortar specimens, so the formula composition is designed to be calcium-aluminum-silicon system, ingredient mixing and solid waste application. The combination of the three greatly reduces the cost budget.
[0090] 3. The present invention provides a new way for resource utilization of solid waste such as desulfurized gypsum, mineral powder, slag, ferrosilicon ash, etc.
[0091] The main characteristics of cementitious materials are light bulk density, high strength, high refractoriness, high refractoriness under load, good chemical stability, small specific surface area, etc. After adding solid waste desulfurization gypsum, cement clinker, mineral powder / water slag, ferrosilicon ash and other raw materials, adding alkali-activated catalyst to increase the flexural strength and compressive strength of cement mortar specimens provides a new technical support for comprehensive utilization, and can obtain good environmental benefits; the present invention makes solid waste desulfurization gypsum, water slag and ferrosilicon ash "turn waste into treasure", which helps to improve the comprehensive performance of concrete.
[0092] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0093] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A cementitious material for comprehensive utilization of solid waste, characterized in that: It comprises a gelled main material and an alkali-activated catalyst, wherein the weight of the alkali-activated catalyst accounts for 5-9% of the weight of the gelled main material; The cementitious main material comprises the following raw materials in parts by weight: 0.05-0.15 parts of cement clinker powder, 0.05-0.15 parts of desulfurized gypsum, 0.1-1 parts of slag / mineral powder, 0.1-0.15 parts of ferrosilicon ash, and 0.0008-0.16 parts of reinforcing additives.
2. The cementitious material for comprehensive utilization of solid waste according to claim 1, characterized in that: The reinforcing aid consists of 0.004-0.008 parts by weight of calcium oxalate and 0.004-0.008 parts by weight of sodium thiosulfate.
3. The cementitious material for comprehensive utilization of solid waste according to claim 1, characterized in that: The alkali-activated catalyst is calcium carbide or calcium hydroxide.
4. A method for preparing a cementitious material for comprehensive utilization of solid waste according to any one of claims 1 to 3, characterized in that: The following steps are involved: S1. Mixing ingredients: grind and sieve the dried cement clinker powder, desulfurized gypsum, slag / mineral powder, and ferrosilicon ash through a ball mill for later use; S2. Dispersing and mixing: weighing the raw materials of the gelling main material according to any one of claims 1 to 3 and uniformly mixing them together to obtain the gelling main material, and then adding 5 to 9% of the weight of the gelling main material to activate the catalyst to obtain the gelling dispersion; S3, mechanical forming: adding water to the gelled dispersion obtained in S2 and stirring to form mortar; S4, mechanical compaction: the mortar obtained in S3 is formed into a test mold and compacted to obtain a mortar test block; S5, curing: curing the mortar test block obtained in S4; S6. Finished product: taking out the test block sample cured in S5 and demoulding it to obtain the cementitious material test block sample for comprehensive utilization of solid waste.
5. The method for preparing a cementitious material for comprehensive utilization of solid waste according to claim 4, characterized in that: In S1, cement clinker powder, desulfurized gypsum, slag / mineral powder, and ferrosilicon ash are dried in an electric blast drying oven at 90°C to 110°C; and the powder is crushed by ball mill and passed through a 200-mesh sieve, with the residue on the sieve being less than 5%.
6. The method for preparing a cementitious material for comprehensive utilization of solid waste according to claim 4, characterized in that: In S3, a mortar mixer is used for stirring and molding, and after the gelling dispersion is stirred for 5 minutes to 8 minutes, water is added to the mixed raw materials and stirring is continued, wherein the mass ratio of the gelling dispersion to water is 4:1, and the total stirring time range of the mortar mixer is controlled within 10 to 15 minutes.
7. The method for preparing a cementitious material for comprehensive utilization of solid waste according to claim 4, characterized in that: The mechanical compaction process of S4 specifically includes: After the mortar is prepared, it is immediately molded. The empty test mold and mold sleeve are fixed on the vibration table. Use a spoon to load the mortar into the test mold in two layers directly from the mixing pot. When loading the first layer, put about 300g of mortar in each groove. Use a large spreader vertically placed on the top of the mold sleeve to spread the material layer back and forth along each mold groove once, then vibrate for 60s, then load the second layer of mortar, spread it flat with a small spreader, vibrate for 180s, resonate for 240s, remove the mold sleeve, take down the test mold from the vibration table, and mark the test mold number.
8. The method for preparing a cementitious material for comprehensive utilization of solid waste according to claim 7, characterized in that: The maintenance process of S5 specifically includes: The marked mortar test blocks shall be immediately placed horizontally or vertically in 20±1℃ water for curing, and the water shall be in contact with the six surfaces of the mortar test blocks; during the curing period, the distance between the mortar test blocks and the water depth on the upper surface of the mortar test blocks shall not be less than 5mm.
Citation Information
Patent Citations
Alkali-activated blast furnace slag gel material and preparation method thereof
CN108203251A
Preparation method of enhanced alkali-free liquid accelerator
CN109437654A
High-strength and high-performance concrete pavement brick admixture and preparation method thereof
CN115959853A
Low-carbon high-strength Portland slag cement as well as preparation method and application thereof
CN116621476A
High-performance solid waste-based cementing material and preparation method thereof
CN117700189A